Konstruksi ‘Bentuk Tubuh Perempuan’ Dalam Iklan Televisi - Endah Murwani (Universitas Multimedia Nusantara, 2010)
The purpose of this research is to explain how mechanism of construction about healthy body shape created throughout advertising. The base theory which be used is social feminism with Critical Discourse Analysis. Result of the research showed that strategy of distinction and dramatization appear from power relations between subject in field of advertising production. Symbolic image about slim and healthy body shape for woman which are producted in advertising, is assumpted by peoples as cultural arbitrary. This social condition is being possible because there is a suitability between social mindset and advertising symbolic image. Keywords : symbolic image, body shape for woman, advertising